2022
DOI: 10.3389/fphar.2022.841981
|View full text |Cite
|
Sign up to set email alerts
|

Morus alba L. (Sangzhi) Alkaloids Promote Insulin Secretion, Restore Diabetic β-Cell Function by Preventing Dedifferentiation and Apoptosis

Abstract: Background:Morus alba L. (Sangzhi) alkaloids (SZ-A), extracted from the Chinese herb Morus alba L. (mulberry twig), have been shown to ameliorate hyperglycemia in type 2 diabetes and have been approved for diabetes treatment in the clinic. However, their versatile pharmacologic effects and regulatory mechanisms are not yet completely understood.Purpose: This study explored the protective effects of SZ-A on islet β cells and the underlying mechanism.Methods: Type 2 diabetic KKAy mice were orally administered SZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Mulberry total biotobasine significantly increased the abundance of microbiota that promote SCFA production such as Erysipelotrichaceae and Bacteroides and reduced the abundance of harmful microbiota such as Desulfovibrio and Rikenellaceae . Therefore, mulberry total biotobasine promotes insulin secretion and ameliorates the β cells of diabetes rats’ dysfunction and mass reduction both in vivo and in vitro ( 48 ).…”
Section: Effects Of Chinese Herb Ingredients On Intestinal Microbiotamentioning
confidence: 99%
“…Mulberry total biotobasine significantly increased the abundance of microbiota that promote SCFA production such as Erysipelotrichaceae and Bacteroides and reduced the abundance of harmful microbiota such as Desulfovibrio and Rikenellaceae . Therefore, mulberry total biotobasine promotes insulin secretion and ameliorates the β cells of diabetes rats’ dysfunction and mass reduction both in vivo and in vitro ( 48 ).…”
Section: Effects Of Chinese Herb Ingredients On Intestinal Microbiotamentioning
confidence: 99%
“…Terefore, the search for safe and efective novel drugs to prevent and treat insulin secretion disorders has been a major research focus worldwide. In recent years, natural drugs such as mulberry alkaloids, cordycepin, and berberine have received attention for their potential in improving insulin secretion [27][28][29]. Cafeic acid dimethyl ether (CADE), also known as methyl ferulic acid, is a bioactive monomer extracted from traditional Chinese herbs [30].…”
Section: Introductionmentioning
confidence: 99%
“…This pharmacological feature is conducive to faster and better control of postprandial blood glucose, while greatly reducing adverse reactions such as flatulence and exhaust in East Asian patients consuming carbohydrates as their staple food (Nojima et al, 1998;Liu et al, 2021). In addition to selectively inhibiting intestinal a-glucosidase, an in-depth study of the mechanism underlying the effects of SZ-A found that exerts multiple in vitro and in vivo pharmacological effects on the regulation of pancreatic islet ß-cell function, insulin resistance, lipid metabolism, intestinal flora, and inflammation (Cao et al, 2021;Liu et al, 2021;Chen et al, 2022;Lei et al, 2022;Sun et al, 2022). In a previous study, the therapeutic effects and mechanism of action of SZ-A on lipid metabolism were explored in high-fat diet (HFD)-induced obesity and non-alcoholic fatty liver disease (NAFLD) mice.…”
Section: Introductionmentioning
confidence: 99%